Gender Peer Effects in School, a Birth Cohort Approach - Antonio Ciccone; Walter Garcia-Fontes (University of Mannheim, Department of Economics, 2014)
We propose estimating gender peer effects in school by exploiting within-school variation in gender composition across birth cohorts. Our approach differs from the existing literature, which exploits variation in gender composition at a given grade level in different years. We argue that the birth cohort approach is a useful alternative as the grade level approach generally yields spurious gender peer effects when there is grade retention. The birth cohort approach applied to primary schools in Spain indicates statistically significant positive gender peer effects of girls on boys' academic achievement and statistically insignificant effects of girls on girls' achievement.
urn:nbn:de:bsz:180-madoc-368471
Keywords: 330